2019
DOI: 10.1021/acs.langmuir.8b04169
|View full text |Cite
|
Sign up to set email alerts
|

Microfluidic Formation of Hydrogel Microcapsules with a Single Aqueous Core by Spontaneous Cross-Linking in Aqueous Two-Phase System Droplets

Abstract: We report a simple process to fabricate monodisperse tetra-arm poly(ethylene glycol) (tetra-PEG) hydrogel microcapsules with an aqueous core and a semi-permeable hydrogel shell through the formation of aqueous two-phase system (ATPS) droplets consisting of dextran (DEX)-rich core and tetra-PEG macromonomer-rich shell, followed by spontaneous cross-end coupling reaction of tetra-PEG macromonomers in the shell. Different from conventional techniques, this process enables for the continuous production of hydrogel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(54 citation statements)
references
References 52 publications
0
52
0
Order By: Relevance
“…the aqueous two-phase emulsion system, when the two aqueous phases used are meticulously selected [ 41 , 42 ]. As such, it has been demonstrated that it was possible to directly write [ 43 ] or print [ 44 ] an aqueous pattern within another aqueous bath, or produce droplets using microfluidic devices [ [45] , [46] , [47] , [48] , [49] ]. The unique advantage of biocompatibility of the aqueous two-phase emulsion system allows it to be used in the presence of cells without exerting any toxicity otherwise imposed by the organic solvents in conventional emulsions.…”
Section: Resultsmentioning
confidence: 99%
“…the aqueous two-phase emulsion system, when the two aqueous phases used are meticulously selected [ 41 , 42 ]. As such, it has been demonstrated that it was possible to directly write [ 43 ] or print [ 44 ] an aqueous pattern within another aqueous bath, or produce droplets using microfluidic devices [ [45] , [46] , [47] , [48] , [49] ]. The unique advantage of biocompatibility of the aqueous two-phase emulsion system allows it to be used in the presence of cells without exerting any toxicity otherwise imposed by the organic solvents in conventional emulsions.…”
Section: Resultsmentioning
confidence: 99%
“…After mixing, the gels can be shaped during polymerization in molds or allowed to gel in situ at injection sites for in vivo applications. Recently, microfluidic devices have been used to produce tetra‐PEG gels as MSs 11 …”
Section: Introductionmentioning
confidence: 99%
“…Microfluidic techniques have a number of appealing features, since it allows a high control over the diameter and morphology of the cell encapsulation matrix. However, it requires a high gelation capacity of the encapsulation matrix solution, which limits the list of available biomaterials [13, 14]. Moreover, oil is often used as a continuous phase to aid forming droplets, which is not a suitable choice for biomedical applications [12].…”
Section: Introductionmentioning
confidence: 99%